(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the research paper is to use a feminist viewpoint to demonstrate the roles and traditions in Anita Desai’s Fasting, Feasting. Uma and her younger sister Aruna are growing up in a traditional Indian home in a tiny Indian village in the late 1970s. Their parents are simply referred to as Mama and Papa, and they attempt to influence their daughters’ futures by teaching them conventional feminine domestic skills. Despite her poor academic performance, Uma enjoys going to her convent school and has little interest in marriage and housework. Uma receives little tolerance from Mama and Papa. Papa, a middle-government magistrate with a fragile ego dominates his family life by dictating the family’s daily activities and everyone’s futures. Priding herself as the wife of an important man, Mama cooperates with Papa on almost every issue.